6 3/4 I think is a possible answer
y = x^2 -4x
x = -1
y = (-1)^2 - 4×-1=1+4 = 5
x= 0
y = (0)^2 - 4×0 = 0
x = 1
y = 1^2 -4×1 = 1-4 = -3
x = 2
y = 2^2 -4×2 = 4-8 = -4
x=3
y = 3^2 - 4×3 = 9-12 = -3
x = 4
y = 4^2 - 4×4 = 16 - 16 = 0
now 2nd equation
y = 2x^2 + x
x = -2
y = 2 (-2)^2 + (-2)= 8-2 = 6
x = -1
y = 2 (-1)^2+(-1)= 2-1 = 1
x = 0
y = 2(0)^2 +0 = 0
x = 1
y = 2 (1)^2 + 1 = 3
x = 2
y = 2(2)^2+2= 8 + 2 = 10
Answer:
a
Step-by-step explanation:
divide 9 and 6 each by 3 and bam you got a 2x3 poster
<span>If the tip, t, varies directly with the number of guests, g, then
it means that any change in tip there is a corresponding change in the
number of guests. When the tip increases the number of guests increases
as well. Therefore,
t </span>α g
To change the it to equal sign, we incorporate a proportionality constant, k.
t =<span> kg
</span>
This equation will represent the relation of t to g